Deep penetrating nevus: A distinct variant of melanocytic nevus - Aparna Gupta; P S Srilatha; Niveditha Suvarna; Lakshmi Rao (Wolters Kluwer Medknow Publications, 2011)
Deep penetrating nevus (DPN) is a variant of melanocytic nevus which goes unrecognized due to its relative rarity and may be misinterpreted as malignant melanoma. It commonly presents in young adults as a dark pigmented lesion on the face, neck, or shoulder. A 60-year-old lady presented with a mole over the left arm of 8 years duration. A biopsy of the lesion was performed under the clinical impression of a compound nevus with suspicion of malignancy. Based on the histologic features, a diagnosis of DPN was put forward.